Level of high sensitivity troponin I and its correlation with hemodialysis vintage – A pilot study - Saloni Malik; Manisha Naithani; Anissa Atif Mirza; Sharon Kandari; Suman KM; Gaurav Shekhar Sharma (Asian Journal of Medical Sciences, 2024)
Background: Renal replacement therapy (RRT) is advised in end-stage renal disease, the last stage of chronic kidney disease (CKD). RRT includes maintenance hemodialysis (MHD)/peritoneal dialysis/renal transplant. The requirement for MHD is annually escalating in India. It is important to note that over 80% of patients receiving MHD have at least one cardiac disease at the time of dialysis initiation, such as ischemic heart disease, congestive cardiac failure, and arrhythmias. Aims and Objectives: The present study aimed to study high-sensitivity cardiac troponin I (hs-cTnI) serum level as a marker of cardiovascular injury in patients receiving MHD. It was an attempt to envisage a correlation between serum hs-cTnI and hemodialysis (HD) vintage (duration since initiation of dialysis till date). Materials and Methods: We enrolled 40 patients. Group 1 included those who had received MHD for ≤24 months, and Group 2 included those who had received MHD for more than 24 months. Results: We found no significant difference between the two groups’ clinical characteristics and demographic features. The pre-and post-HD serum hs-cTnI values of all patients were recorded. The serum hs-cTnI levels were found to be elevated in 34 out of 40 patients’ post-dialysis, and the result was statistically significant (P=0.0001). Conclusion: The present study has encouraging results, with values of hs-cTnI raised in post-dialysis samples; however, the levels did not correlate with HD vintage. Further studies with larger sample sizes and longer follow-ups would provide more detailed information on hs-cTnI’s role as a marker for HD-induced cardiac damage.